2016
DOI: 10.1002/cptc.201600015
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight‐Driven Overall Water Splitting by the Combination of Surface‐Modified La5Ti2Cu0.9Ag0.1S5O7 and BaTaO2N Photoelectrodes

Abstract: A photoelectrochemical (PEC) cell composed of an Al‐doped La5Ti2Cu0.9Ag0.1S5O7 (Al‐LTCA) photocathode and a BaTaO2N (BTON) photoanode was employed for overall water splitting. The surface of the Al‐LTCA photocathode was modified first with CdS by a chemical bath treatment (CBT) and subsequently with TiO2 and Pt (to form Pt/TiO2/CBT‐CdS/Al‐LTCA). The modified photocathode Pt/TiO2/CBT‐CdS/Al‐LTCA showed a significantly enhanced photocurrent for the PEC hydrogen evolution reaction in strongly alkaline aqueous pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 24 publications
3
49
0
2
Order By: Relevance
“…A typical PEC cell is composed of a photoanode and a photocathode that are electrically connected to one another and immersed in an aqueous electrolyte solution . The solar‐to‐hydrogen energy conversion efficiency (STH) of a PEC cell is maximized by adjusting the light‐receiving area and the common operational potential of both photoelectrodes in order to balance the photocurrent from each . A PEC cell having a tandem configuration in conjunction with a stacked structure, incorporating a front side transparent photoelectrode along with a second photoelectrode that responds to the light transmitted through the front side photoelectrode, could potentially allow efficient water splitting .…”
Section: Figurementioning
confidence: 99%
“…A typical PEC cell is composed of a photoanode and a photocathode that are electrically connected to one another and immersed in an aqueous electrolyte solution . The solar‐to‐hydrogen energy conversion efficiency (STH) of a PEC cell is maximized by adjusting the light‐receiving area and the common operational potential of both photoelectrodes in order to balance the photocurrent from each . A PEC cell having a tandem configuration in conjunction with a stacked structure, incorporating a front side transparent photoelectrode along with a second photoelectrode that responds to the light transmitted through the front side photoelectrode, could potentially allow efficient water splitting .…”
Section: Figurementioning
confidence: 99%
“…Oxysulfides La 5 Ti 2 CuS 5 O 7 (LTC) and La 5 Ti 2 Cu 0.9 Ag 0.1 S 5 O 7 (LTCA) have emerged as promising photocathode materials, with the latter absorbing light up until 710 nm and demonstrating PEC H 2 production from aqueous solution, with an onset potential of 0.8 V versus the reversible hydrogen electrode (RHE) when using Pt as a co‐catalyst . Surface modification of LTC and LTCA photocathodes with thin TiO 2 layers improves their activity due to enhanced charge separation, and layers of amorphous TiO 2 have been shown to protect LTCA under strongly alkaline (pH 13) conditions …”
Section: Figurementioning
confidence: 99%
“…As imilar effect to that achieved with I-III-VI 2 compounds was obtained via surface modification with at hin (40-100 nm) CdS layer in conjunction with variousc halcogenide-based photocathode materials, includingC dTe, Cu 2 ZnSnS 4 and (ZnSe) 0.85 (CuIn 0.7 Ga 0.3 Se 2 ) 0.15 . [24][25][26][27][28][29][30][31] It should be noted that the Cd species diffusei nto the absorber during the chemical bath deposition of the CdS, resulting in the formation of Cd Cu antisites. [32] Because these defects act as donors, the regions con-tainingC d Cu antisites will exhibit n-type properties.…”
Section: Control Of Built-in Potentialmentioning
confidence: 99%
“…The authors also reported that the 0.98 eV offset between CuGaSe 2 and CdS can promote the selective diffusion of electrons into the CdS layer, as discussed in Section 3.2 below. A similar effect to that achieved with I‐III‐VI 2 compounds was obtained via surface modification with a thin (40–100 nm) CdS layer in conjunction with various chalcogenide‐based photocathode materials, including CdTe, Cu 2 ZnSnS 4 and (ZnSe) 0.85 (CuIn 0.7 Ga 0.3 Se 2 ) 0.15 . It should be noted that the Cd species diffuse into the absorber during the chemical bath deposition of the CdS, resulting in the formation of Cd Cu antisites .…”
Section: Roles Of Surface Modificationsmentioning
confidence: 99%